Dreyer's English : an utterly correct guide to clarity and style - Dreyer, Benjamin (2019)
"Authoritative as it is amusing, this book distills everything Benjamin Dreyer has learned from the hundreds of books he has copyedited, including works by Elizabeth Strout, E. L. Doctorow, and Frank Rich, into a useful guide not just for writers but for everyone who wants to put their best foot forward in writing prose. Dreyer offers lessons on the ins and outs of punctuation and grammar, including how to navigate the words he calls 'the confusables,' like tricky homophones; the myriad ways to use (and misuse) a comma; and how to recognize--though not necessarily do away with--the passive voice. (Hint: If you can plausibly add 'by zombies' to the end of a sentence, it's passive.) People are sharing their writing more than ever--on blogs, on Twitter--and this book lays out, clearly and comprehensibly, everything writers can do to keep readers focused on the real reason writers write: to communicate their ideas clearly and effectively. Chock-full of advice, insider wisdom, and fun facts on the rules (and nonrules) of the English language, this book will prove invaluable to everyone who wants to shore up their writing skills, mandatory for people who spend their time editing and shaping other people's prose, and--perhaps best of all--an utter treat for anyone who simply revels in language"--
The life-changing magic of tidying up (your prose) -- Rules and nonrules -- 59 assorted things to do (or not to do) with punctuation -- 1, 2, 3, go: the treatment of numbers -- Foreign affairs -- A little grammar is a dangerous thing -- The realities of fiction -- Notes on, amid a list of, frequently and/or easily misspelled words -- Peeves and crotchets -- The confusables -- Notes on proper nouns -- The trimmables -- The miscellany.
Includes bibliographical references and index.
Keywords: Authorship -- Technique